Strategic Planning of Ecotourism Management System Using Ward and Peppard Framework - Yerik Afrianto Singgalen (Journal of Information System and Informatics, 2022)
The strategic planning of the Dodola Island, Tourism destination management system is the development of previous research concerning transformation in the vegetation index value of the mangrove ecotourism area and recommendations for the rehabilitation of mangrove zones to maintain the ecological sustainability of mangroves. In addition to the environmental, socio-economic, and socio-cultural aspects, it is also necessary to develop a destination management system. This research uses the Ward and Peppard framework to design the system by considering the existing ecological, socio-economic, socio-cultural conditions, resource availability, tourist behaviour, and destination management capabilities. The instruments used in the Ward and Peppard framework analysis are Value Chain Analysis, Porter’s Five Force Model, SERVQUAL, PESTEL and SWOT Analysis, Ecopreneurship Model, and IT Balanced Scorecard. The Ward and Peppard framework describes the need for information systems to mobilise the Small and Medium Enterprise activity in the mangrove ecotourism area. Furthermore, the amenity, accommodation, and local transportation accessibility are recommended. These systems are designed based on the ecopreneurship model to optimise the management of tourism destinations known as SIMANGROVE on Dodola Island, Morotai Islands Regency, Indonesia.